The correlation between Ki-67 with other prognostic factors in breast cancer: A study in Iranian patients - Seyed-Hamid Madani; Mehrdad Payandeh; Masoud Sadeghi; Hajar Motamed; Edris Sadeghi (Indian Journal of Medical and Paediatric Oncology)
Context: Despite the fact that breast cancer (BC) is a major health issue, very few studies describe its characteristics in the Middle East. Aim: The aim of this study was to evaluate the use and value of Ki-67 as a prognostic marker in BC and associations between Ki-67, clinical, and histopathological parameters were evaluated. Subjects and Methods: In a retrospective study, 260 BC women and invasive ductal carcinoma were included to our study in Kermanshah city, Iran. Age, tumor size, lymph node involvement, histological grade, nuclear grade, and vascular invasion were other factors that determined in a lot of patients. Results: The mean age at diagnosis was 47.6 years (range, 24-84 years) with 100% female. Of 243 patients that tumor size was determined for them, 207 patients (85.2%) had tumor size ≥ 2 cm, and 36 patients (14.8%) had size <2 cm and also of 237 patients, 47 patients (19.8%), 140 (59.1%), and 50 (21.1%) had histological grades I, II, and III, respectively. There is significant correlation between Ki-67 with nuclear grade, human epidermal growth factor receptor 2 (HER2), and p53 (P < 0.05). Based on this result, more patients with Ki-67 ≥ 20% have higher nuclear grade, p53-positive, and HER2-positive. There was correlation between Ki-67 with type of tumor (P = 0.009). Conclusions: The higher Ki-67 has a direct significant correlation with higher nuclear grade, p53-positive, and HER2-positive. Furthermore, triple negative patients have higher Ki-67 compared to other subtypes.